Demystifying the "Sunk Cost Fallacy": When Considering Fixed Cost in Decision-Making is Reasonable - Krämer, Andreas (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
Economic theory explains that when making decisions, historical costs should be irrelevant. When people are influenced by sunk costs in their decision-making, they are said to be committing the “sunk cost fallacy”, summarized by Kelly (2004) as the conjunction of two claims: (1) Individuals often do give weight to sunk costs in their decision-making, and (2) it is irrational for them to do so. Based on three studies both aspects are investigated (Amazons loyalty program Prime, German railways discount card BahnCard and decisions to use the own car when making long-haul trips). There are strong indicators that in all three examples fixed costs play a crucial role when consumers make decisions; and doing so is not necessarily irrational.